Efeito de fosfito de potássio em doenças foliares do milho - Silva, João Batista Gonçalves Dias da (2011)
Corn employs a strategic key in the chain production of animal protein (meat, eggs, and byproducts) which consumption grows every year. The impact of leaf disease in corn crop is growing continuously fostering higher survival of pathogens in the field. Then, the objective of this work was to evaluate in the field the effect of potassium phosphite application to control leaf diseases on productivity and occurrence of sour grains. It was carried out three trials at Cocari Technological Center, Mandaguari, PR, at different times, to eleven corn hybrids. The following treatments were compared: T1 - phosphite 2.0 L.ha-1 for V6 phenological stage, T2 - phosphite 2.0 L.ha-1 for V10 stage (pretasseling), T3 - phosphite 1.0 L.ha-1 for V6 and V10 stages, T4 - phosphite 2.0 L.ha-1 for V6 and V10 stages, T5 - phosphite 1.0 L.ha-1 for V6 stage followed by epoxiconazole + piraclostrobina (Ópera®) 0.6 L.ha-1 + mineral oil (Assist®) at 0.5% for V6 stage, T6 - fungicide 0.6 L-ha-1 + mineral oil at 0.5 % for V10 stage, T7 - control having no application. All phosphite potassium treatments reduced the rate of severity and/or AACPD of diseases, and showed higher efficiency to Cercospora stain control, followed by white stain, Helminthosporioses common, and less for blight. The treatment T4 followed by T2 were the most promising, although the fungicide resulted in lower rates of severity and AACPD and the best levels of disease control. The treatment did not reduce the incidence of sour grains, but resulted in higher productivity.